A Cross-Cultural Web Usability Analysis of Asian Countries’ Official Tourism Websites - Jaslin Md. Dahlan; Awang Rozaimie Awang-Shuib (Bina Nusantara University, 2011)
Demands for tourism websites from worldwide providers is now surging. It is a quality measurement of advertising, information providing and persuasive marketing all in one. The evaluation of website’s usability illuminates the specific strengths and weaknesses of each websites studied. A selection of 39 Asian countries was studied. A criterion for selection was for the country to have an official tourism website hosted and managed by a government agency. This non-commercial study is to ensure the reliability of information. A walkthrough content analysis method was used for the evaluation. The month-long evaluation experiments the seven elements of webs’ features and functions with 44 attributes. Results were varied with highest and lowest scores were tabulated and discussed. Tourism websites that scored the highest overall and categorical sections obviously placed tourism as their main industry of the economy. The study is limited by the availability of the websites during the evaluation period. No re-evaluation on another date was done, as to avoid biasness.